Retrospective study on adverse drug reaction In a tertiary care hospital - A.TAMIL BHARATHI,; N.SIVASANKARI,; MS. RAJESWARI.H,; DR. B. SREELEKHA, (International Journal of Pharma and Bio Sciences, 2016)
In any healthcare organization patient safety is the prime responsibility of all health care providers. An adverse drug reaction (ADR) is any noxious or unintended and undesired effect of a drug, which occurs at doses used in humans for prophylaxis, diagnosis or therapy. The main aim of the study was to monitor the adverse drug reaction in a tertiary care hospital, to identify the type of drug leading to adverse drug reaction and the adverse effects. A retrospective study was carried out in a tertiary care teaching hospital, Chennai. Adverse drug reaction reported from the period January 2015 to December 2015 was collected. One hundred and forty-six adverse drug reactions were identified. ADR was assessed by WHO causality assessment scale. 34/146(23.5%) of the reported ADRs were in the age group of 31-45 yrs. Majority of them were among males 90/146 (62%). 96/146 (64.4%) patients had serious ADR. Casualty assessment reveals that 61/146 (40%) of the identified ADR are probable. The major source for ADRs were antibiotics 110/146 (75.34%) and when administered intravenously. Intugumentary system was the most affected 90/146 (61.6%) by ADRs. The order of appearance of ADR is 34/146 (23.2%) urticarial rash>22/146 (15%) erythematous rash>20/146 (13.7%) nausea and vomiting>16/146 (11%) patient reported vertigo>12/146(8.2%) anaphylactic reaction>10/146(6.8%) exanthematous rash, puffiness of face and nephrotoxicity>7/146(4.8%) erythema multiformis>3/146(2%) macula papular rash. In our study, antibiotics remained the major source of adverse reactions when administered intravenously. Hence, vigilance during drug administration is needed at healthcare settings to avoid the morbidity and mortality.